Analisis Komposisi Mineral Lempung dan Maturitas Material Organik Daerah Balikpapan Selatan, Kota Balikpapan, Kalimantan Timur - Jamaluddin Jamaluddin; Agus Wiramsya Oscar; Nijusiho Manik; Emi Prasetyawati Umar (Universitas Halu Oleo, 2025)
The research aims to analyze the influence of clay mineral composition on the thermal evolution of source rock in the South Balikpapan area, Balikpapan City, East Kalimantan. Mudstone samples were analyzed by vitrinite reflectance (Ro), X-ray diffraction (XRD) and scanning electron microscopy (SEM). XRD analysis results show that the predominant clay minerals in the mudstone are mixed illite/smectite (35-42%), kaolinite (30-39%), illite (18-23%), and chlorite (5-10%). The predominant mineral presence of illite/smectite indicates a high heat retention capability. This plays an important role in the process of diagenesis and thermal transformation. High heat retention allows for localized temperature increases that further influence the thermal evolution of the host rock. The kaolinite mineral, which reaches 30-39%, contributes to the thermal stability of the host rock due to its inert nature in the medium temperature range. Meanwhile, the presence of illite minerals (18-23%) also supports thermal stability but with a smaller role than kaolinite. Otherwise, chlorite (5-10%) can increase the chemical reactivity of minerals under high temperature conditions, potentially triggering mild metamorphic reactions in rocks. The Ro values obtained from the samples range from 0.33% to 0.47%, which indicates a low to medium level of thermal maturity. This maturity level indicates that the mudstone rocks in the South Balikpapan area have not reached the optimal condition to produce hydrocarbons. These vitrinite reflectance values correspond to the estimated maximum temperature that the rocks have experienced, which is likely not high enough to trigger the formation of significant amounts of oil or gas.